Interfering with Host Proteases in SARS-CoV-2 Entry as a Promising Therapeutic Strategy - Müller, Patrick; Maus, Hannah; Hammerschmidt, Stefan J.; Knaff, Philip Maximilian; Mailänder, Volker; Schirmeister, Tanja; Kersten, Christian (Current Medicinal Chemistry, 2022)
Due to its fast international spread and substantial mortality, the coronavirus disease COVID-19 evolved to a global threat. Since there is currently no causative drug against this viral infection available, science is striving for new drugs and other approaches to treat the new disease. Studies have shown that the cell entry of coronaviruses into host cells takes place through the binding of the viral spike (S) protein to cell receptors. Priming of the S protein occurs via hydrolysis by different host proteases. The inhibition of these proteases could impair the processing of the S protein, thereby affecting the interaction with the host-cell receptors and preventing virus cell entry. Hence, inhibition of these proteases could be a promising strategy for treatment against SARSCoV- 2. In this review, we discuss the current state of the art of developing inhibitors against the entry proteases furin, the transmembrane serine protease type-II (TMPRSS2), trypsin, and cathepsin L.
Keywords: COVID-19